ANALYSIS OF THE STATE OF DEVELOPMENT OF TEXTILE ENTERPRISES IN UZBEKISTAN AND TRENDS OF THEIR EMPLOYEE MANAGEMENT (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article reveals the essence of the concept of personnel management. At the same time, the approaches of scientists to personnel management are highlighted and general conclusions are drawn. The methodological significance of personnel management in enterprises is revealed. An analysis of the number of jobs in the economy of Uzbekistan, in particular in the textile industry, was carried out.
Keywords: personnel management, personnel, personnel, aspects of personnel management, economically employed population.